Pengaruh Tujuan, Tema Dan Tempat Acara Terhadap Kesuksesan Acara Pada Kegiatan Parents Day (Jurnal Ilmiah Pariwisata, 2016)
Parents day is an annual event that began in STP Trisakti since 1990. The originator of this event was the team of lecturers in food and beverage departement to finalize the initial objective, the students in the field of food and beverage service before actually entering the hospitality industry when they do the job training. Event in this category are held for educational purposes, such as training work shops or seminars, or for scientific collaboration. Therefore, the implementation of this event is done when the students are in the fifth semester. There are numoerous elements that need to be considered in developing an event concept, include event purpose, event theme and venue.. The method of this research using quatitative descriptive to describe the effect between response modifiers with the factors that effect more than one predictor. The total of the parents that come to the parents day used as the population . there are 250 people. Therefore total population is applied. Data in this research are the primary data consist of the identity and the characteristics of the parents that come to the event, such as gender and age. Based on the characteristics of the respondents show based on gender that 59,6% is male and 40,4% is female, and there are 77,2 % of respondents aged 39 – 44 years. The research design is focused on the affection of event purpose, event theme and venue to event success. And the result of this research found that event concept has significant and positive to make the event success. The result analysis show that variable of the event concept has a significant value 0,00, with each of sub variable are event purpose 0,007, even theme 0,007, event venue 0,009 where the values is less than 0.05